Unit Cost Analysis of National Health Insurance in Inpatients during COVID-19 Pandemic at Pelengkap Medical Center Hospital, Jombang, East Java - Prameswari, Galuh Ayu Dyah; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: In the era of Universal Health Coverage (UHC) as it is now, it is no longer a strange thing. The Indonesian government is preparing for the fulfillment of Universal Health Coverage (UHC) through the National Health Insurance program. The challenge that occurs is that hospitals that work together with BPJS Health are required to be able to carry out quality and cost control. The purpose of this study was to analyze the factors that influence the gap between the BPJS Health Inpatient unit cost rates and the INA CBGs package rates at complementary medical center hospitals in the pandemic era.Subjects and Method: The study was conducted with an analytical observational study design using a crosssectional approach carried out at the Complementary Medical Center Hospital in February March 2022. In a one year period, 204 billing for inpatients using BPJS Kesehatan were selected using a random sampling method. The dependent variable is the difference between the INA CBG package rates and the unit cost. The independent variables were readmission patients, surgery, extra doctors, intensive care, and special drugs. Data were collected by taking billing unit cost of patients at the hospital and analyzed using logistic regression. Results: The results showed that readmission, surgery, and intensive action had an effect on reducing the difference between INA CBG payments and unit cost and was statistically significant. INA CBG payments for patients with readmission were on average Rp 1,142,409 lower than the unit cost (b= 1,142,409; 95% CI= 1,864,753 to 420,066; p= 0.002), while the average surgical procedure was Rp 343,067 lower than the unit cost (b=343,067; 95% CI= 727,550 to 41,414; p = 0.80) and the average intensive action was Rp 1,226,861 lower than the unit cost and the effect was statistically significant (b= 1,226,861; 95% CI= 1,904,739 up to 538,984; p<0.001). Meanwhile, special drugs and extra doctors did not have a statistically significant effect, special drugs (b= 450,282; 95% CI= 1,662,453 to 761,889; p= 0.645) and extra doctors (b=159,838; 95% CI= 537,507 to 253,507; p = 0.447).Conclusion: Patient readmission and surgical procedures affect the difference in INACBGs package rates and unit costs. Keywords: inpatient unit cost, health bpjs.Correspondence: Galuh Ayu Dyah Prameswari. Masters Program in Public Healrh, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: galuh.mahesa@gmail.com. Mobile: 0895358233743.Journal of Health Policy and Management (2022), 07(03): 210-217 https://doi.org/10.26911/thejhpm.2022.07.03.05